2019
DOI: 10.1044/2019_jslhr-h-18-0480
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Development of Wideband Absorbance and Admittance Through Infancy

Abstract: Purpose The aim of this article was to study the normal longitudinal development of wideband absorbance and admittance measures through infancy. Method Two hundred one infants who passed the newborn hearing screen (automated auditory brainstem response) were tested at birth and then followed up at approximately 6, 12, and 18 months of age. Most infants were of either White (86%) or Asian (11%) descent. At each test session, infants passed tympanometry a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…This study was part of a larger project that followed 753 infants from birth (Myers et al, 2018a(Myers et al, , 2018b(Myers et al, , 2019c…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…This study was part of a larger project that followed 753 infants from birth (Myers et al, 2018a(Myers et al, , 2018b(Myers et al, , 2019c…”
Section: Methodsmentioning
confidence: 99%
“…Although preliminary studies in infants have reported strong performance Myers et al, 2018b;Prieve et al, 2013b), more diagnostic research in this age group is necessary, as WAI could be a valuable tool for identifying middle ear pathology early in childhood. Furthermore, research is needed on different age groups through infancy, as there are large developmental effects on the WAI response that are not yet complete by 24 months of age (Keefe et al, 1993;Kei et al, 2013;Myers et al, 2019c). Ellison et al (2012) included some 12-month-old infants in their study, but the age of the 88 children in the sample ranged from 6 months to 7 years.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations